2015
DOI: 10.1590/0103-8478cr20131458
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização e avaliação das propriedades antioxidantes de filmes biodegradáveis incorporados com polpas de frutas tropicais

Abstract: RESUMO O trabalho teve como objetivo desenvolver e caracterizar embalagens ativas fl exíveis formuladas pela incorporação de polpas de frutas tropicais a uma matriz polimérica

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 14 publications
0
16
0
8
Order By: Relevance
“…Several biopolymers such as polysaccharides, proteins, and lipids have been utilized as polymeric matrixes for the development of alternative biodegradable packaging, owing to their availability, renewability, low cost, environmental friendliness, and biodegradability [7][8][9] . Among such agriculturally sourced materials, starch is considered to be favorable for the development of biocomposites [10,11] . Starch films are particularly characterized by transparency, non-toxicity, and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Several biopolymers such as polysaccharides, proteins, and lipids have been utilized as polymeric matrixes for the development of alternative biodegradable packaging, owing to their availability, renewability, low cost, environmental friendliness, and biodegradability [7][8][9] . Among such agriculturally sourced materials, starch is considered to be favorable for the development of biocomposites [10,11] . Starch films are particularly characterized by transparency, non-toxicity, and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…The solubility values for the açaí films were close to the cassava starch and soy protein 29 films and to the starch films added of acerola pulp at different concentrations 8 where the authors verified that the higher the content of pulp added, the lower the solubility of the film. The solubility of the açaí film are even lower than the value found for biodegradable films with different fruit pulps 65 , which is advantageous. High solubility does not impair film, it may be necessary in the case of films that need to be subjected to contact with water during processing of dehydrated foods.…”
Section: Water Solubility Of Filmsmentioning
confidence: 81%
“…The low tensile strength of the açaí films can be justified by the heterogeneity of the material, which makes it easier to get ruptures at these points. Dantas et al 65 found lower resistance to cassava starch films and fruit pulp. Regarding the deformation, percentages were found from 14.77 to 34.78%, whereas the control film presented 38.61%.…”
Section: Mechanical Traction Testsmentioning
confidence: 94%
“…Films were made following a method described by Dantas et al (2015) and Lorotonda (2002). Water-starch-glycerol mixtures were prepared by varying the glycerol concentration in relation to the starch-water mixture (Table 1).…”
Section: Biodegradable Film Productionmentioning
confidence: 99%
“…Biodegradable packaging is a sustainable development alternative to petrochemical-based products, being generated from renewable resources it can also increase income for local farmers (Arenas, 2012). Developing the use of natural products in biodegradable packaging is of great interest to both industry and society in general, since it brings benefits for food-based industries and the environment (Dantas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%